Hyperglycemia-induced degradation of HIF-1α contributes to impaired response of cardiomyocytes to hypoxia - Ramalho, Ana Rita (2017)
Cardiovascular disease is the leading cause of mortality and morbidity associated with diabetes. Although impairment of the cell response to hypoxia due to destabilization of the transcription factor hypoxia-inducible factor-1α (HIF-1α), which regulates the expression of genes that help cells to cope with low oxygen tension, has been implicated in diabetes-associated disease, the molecular mechanisms involved remain elusive. It is known that hyperglycemia leads to the enhanced production of methylglyoxal (MGO). Therefore, the main objective of this study was to establish whether MGO leads to the degradation of HIF-1α in cardiomyocytes subjected to hypoxia. Methods: The mouse atrial cardiomyocyte cell line, HL-1, was exposed to chemical hypoxia with CoCl2 in the absence or presence of MGO. Cell viability was assessed by MTT assay, and levels of HIF-1 and endogenous ubiquitin conjugates were determined by western blotting. Proteasome activity was analyzed using a specific chymotrypsin-like fluorogenic substrate. Results: The results obtained indicate that MGO induces time- and dose-dependent degradation of HIF-1 accumulated under hypoxia. Additionally, we show that accumulation of endogenous ubiquitin conjugates in the presence of MGO is associated with decreased proteasome activity.Conclusion: Taken together, the results obtained in this study suggest that MGO compromisesthe ability of cells to adapt to low oxygen tensions, by stimulating the degradation of HIF-1 ,likely contributing to the development of diabetes-associated cardiac dysfunction.